The Notion of a Woman in the Work of Stefan the First-Crowned - Đekić, Đorđe; Zarković, Božidar (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
The most frequently mentioned woman in the literary work of Stefan the First–Crowned is the Blessed Virgin, a God pleasing role model whose pursuit leads to the salvation of the soul. She was also a role model to his father, Stefan Nemanja. In addition, she was at the same time the most common example of a role model mother followed by all mothers, as well as his mother Ana and his grandmother. His father’s mother was mentioned but remained nameless. Of the other roles of a woman, in the centre of his attention was the wife of a husband. The context in which he mentioned her was the matrimonial law—penalties for unlawful marriage, unlawful dissolution of marriage, an adulterous woman, and forbidden marriage with sister–in–law. However, no mention was made of the obligations of parents, of a mother towards children, or of the adult children towards mothers. It must be noted that he did not talk much about a woman as a mother, though he did provide some information. It was fragmentary information about the mother–in–law, the widow, but there is no information about a woman–sister, woman–daughter, which is a striking testimony that he was not interested in these aspects of a woman. Apparently, he was only interested in a woman as a God–pleasing role model, among other things, God–pleasing mothers also in the sense of regulating marital relations.